Contribution of occupational therapy for patients with depression / Beitrag der Ergotherapie in der Wahrnehmung von Menschen mit Depression - Treusch Yvonne; Saxer Nadine; Witschi Theresa; Page Julie (Sciendo, 2016)
So far, few studies exist concerning the professional contribution and effects of occupational therapy in people with depression. This contrasts the practical and quantitative contribution of this form of therapy.